Undermined (Hegemonic) masculinity and subjective reconstruction within prostitution - Beatriz Ranea Triviño (Oñati Socio-Legal Series, 2018)
In this article, we analyze how prostitution has been resignified as a scenario of subjective reconstruction for men in a social context of changes. Prostitution is analyzed from a gender and feminist perspective, taking into account how gender inequality makes possible prostitution and how gender inequality is reproduced within prostitution. Also we analyze the construction of the masculinity arguing that masculinity is supported by some bases: identity linked to work and family provider; to the authority of the paterfamilias; to the exercise of violence or the threat of using it; to sexual activity (following androcentric and patriarchal patterns). It is argued that some of these bases have failure and others (violence and sexual activity) have strengthened and prostitution appears at the crossroads between violence and patriarchal sexuality.